Analysis of Chemosensory Genes in Full and Hungry Adults of Arma chinensis (Pentatomidae) Through Antennal Transcriptome - Wu, Shaolong; Deng, Wan; Li, Mi; Xiao, Yansong; Li, Jiaying; Teng, Kai; Xiao, Zhipeng; Li, Xiaohong; Zhou, Zhicheng; Li, Youzhi (Frontiers in Physiology, 2020)
Abstract： Arma chinensis (Hemiptera: Pentatomidae) is a widely distributed and applied predatory insect in China, can effectively control many agricultural and forest pests.Chemosensory genes of prey bugs antennae play crucial roles in food-seeking and mating behaviors. To better understand the olfaction of A. chinensis antennal and identify the major olfaction genes, clear and definite which genes are related to seek food and which genes are related to look for spouse, we sequenced the male and female antennal transcriptomes of this predatory bug respectively in full and hungry condition. We identified 38 OBPs (odorant binding proteins ), 1 CSPs (chemosensory proteins), 1 NPC2 ( Niemann-Pick C2 protein), ORs (3 odorant receptors), 12 IRs (ionotropic receptors), 2 GRs ( gustatory receptors) and 3 SNMPs (sensory neuron membrane proteins), and which were respectively used to construct phylogenetic trees.The qRT-PCR results indicated that the relative transcript levels of AchiGR1, AchiGR2 and AchiOBP28 were higher in female antennae than those in male antennae no matter full or hungry, and AchiOBP13 and AchiOBP16 were more higher only when female A. chinensis were full, which indicated those genes might encode some proteins relating to oviposition selection behavior. (6-8, 12, 20-22, 28 and 34) were more higher only when male A. chinensis were full, indicating those genes might involve to mate searching or recognize the pheromone molecules for male. AchiOBPs31 in hungry male antennae, AchiOBPs (15, 18 and 29) in hungry female antennae and AchiOBPs (3, 4 and 24) in both hungry male and female antennae were significant higher than those in full A. chinensis antennae, indicating those genes might involve to looking for food. In this paper, we first identified and analyzed the differences expression of chemosensory genes in full and hungry A. chinensis antennae, screened five genes related to female oviposition, twelve genes related to male seek spouse and seven genes related to look for foods, which provide basis for further functional studies on the chemoreception system of A. chinensis and useful data for further studies on sex-hormone of predatory insects.